SIGNIFIKANSI OBSERVATORIUM DAN PLANETARIUM DI ERA MODERN - Abdul Kohar (ELFALAKY: Jurnal Ilmu Falak, 2024)
Observatory is a location that is used to observe events related to Outer Space or Earth. The observatory also developed from one generation to the next. The first observatory was founded in the Abbasid period al-Ma'unun, the Syammasiyah observatory. The characteristic of this period is that the observatory aims to produce ephimeris data from the Sun, Moon and planets, and catalog stars. The observatory in early Europe was marked by an observatory that built by Tycho Brahe. He made observations from 1588 to 1591 and he produced a catalog of 777 stars with increased accuracy. The results of this observation are used by Kepler to find the motion of planet ellipses. Furthermore, in the modern era, observatories are characterized by observing celestial bodies using the electromagnetic spectrum. The urgency of observatories in the modern era is as a science institution, as a way of collecting accurate astronomical data, the Royal Greenwich Observatory as a Prime Meridian point and as a way of determining worship times. Whereas, Planetarium is a theater to demonstrate the simulation of the arrangement of stars and the movement of celestial bodies. The Urgency of Planetarium is as an Astronomical Educational Vehicle and as a means of entertainment.